AN EVALUATION OF IMPLEMENTATION CHARACTER EDUCATION PROGRAM AT SENIOR HIGH SCHOOL IN MATARAM CITY - Nugroho, Etika Ariyani (Journal of Education Research in Administration and Management (JERAM), 2017)
The purposes of this study were to evaluate (1) background of character education program implementation on regulations, goal and function; (2) character education program input relate to school culture and teacher competencies; (3) education character program process relate to implementation,monitoring and evaluation, and responsibility; and (4) product, the result of program implementation.This program has been implemented since 2010 in Mataram city- West Nusa Tenggara Province. The results disclosed that the implementation of character education program was need improvement which is indicated by (1) regulations,goal and objective are fulfilled; (2) input component relate to school culture and teacher competencies are partially fulfilled; (3) process component relate to implementation, monitoring and evaluation, and responsibility are partially fulfilled; and (4) product, the result of program implementation relate to students achievement and the internalization of 18 character values are partially fulfilled. It is suggested to improve teacher competencies, family control and manage monitoring-evaluation process.